2021
DOI: 10.3390/environments8120139
|View full text |Cite
|
Sign up to set email alerts
|

Multitemporal Analysis as a Non-Invasive Technology Indicates a Rapid Change in Land Use in the Amazon: The Case of the ITT Oil Block

Abstract: The Amazon Region of Ecuador (ARE) hosts a great variety of biodiversity and ecosystems. These hotspots are internationally recognized for presenting unique fauna and flora found nowhere else in the world. Within the ARE, there is the Yasuní National Park (YNP), a recognized Biosphere Reserve located in the sub-basins of various rivers. The study area is the “ITT Oil Block” (Ishpingo, Tambococha, and Tiputini), situated in the Province of Orellana and superimposed on the YNP. The block has an area of 179,449.5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 62 publications
(65 reference statements)
0
7
0
1
Order By: Relevance
“…Despite the observed land use changes [74], the respondents did not perceive deforestation as a significant risk for them unless it was associated with colonists' claiming the land for agricultural purposes [24,45]. Land rights and the lack of significant community benefits from using their land for oil activity are of great concern for the community members, as reported by Gilbert [75].…”
Section: Oil Exploitationmentioning
confidence: 93%
“…Despite the observed land use changes [74], the respondents did not perceive deforestation as a significant risk for them unless it was associated with colonists' claiming the land for agricultural purposes [24,45]. Land rights and the lack of significant community benefits from using their land for oil activity are of great concern for the community members, as reported by Gilbert [75].…”
Section: Oil Exploitationmentioning
confidence: 93%
“…Donde encontramos valores negativos en las categorías de suelo desnudo con -7,5%, seguido de bosque denso con -1,7% y cuerpos de agua con -1,2%. A partir del año 2001 la superficie forestal ha venido disminuyendo, solo las áreas de infraestructura y agricultura han aumentado hasta 2017, según un estudio empleado en el bloque petrolero ITT (bloque 43) efectuada por (Heredia et al, 2021).…”
Section: Elaboración Del Modelo Prospectivo De Cobertura Vegetal Para...unclassified
“…FAO stated that between 1990 and 2000, Ecuador had the highest deforestation rate, averaging 1.2% year. Consequently, these factors have led to a land-use change, and fragmentation of farms due to population growth (Mena et al, 2006;Heredia-R et al, 2021). Since, Botto-Nuñez et al (2020) found association between forest fragmentation and pathogen spillover by contact with reservoir species (e.g., bats).…”
Section: Introductionmentioning
confidence: 99%